Acid suppressants for managing gastro-oesophageal reflux and gastro-oesophageal reflux disease in infants: a national survey. Issue 7 (22nd February 2018) - Bell, Jane C; Schneuer, Francisco J; Harrison, Christopher; Trevena, Lyndal; Hiscock, Harriet; Elshaug, Adam G; Nassar, Natasha
Abstract : Objectives: To evaluate the diagnosis and management of reflux and gastro-oesophageal reflux disease (GORD) in infants aged <1 year presenting to general practitioners (GPs). Design, setting and participants: A nationally representative, prospective, cross-sectional survey of GP activity in Australia, 2006–2016 (Bettering the Evaluation And Care of Health Study). Annually, a random sample of around 1000 GPs recorded details for 100 consecutive visits with consenting, unidentified patients. Outcome measures: Diagnoses of reflux and GORD and their management including prescribing of acid-suppressant medicines (proton pump inhibitors (PPIs) and histamine receptor antagonists (H2RAs)) and counselling, advice or education. Results: Of all infants' visits, 512 (2.7%) included a diagnosis of reflux (n=413, 2.2%) or GORD (n=99, 0.5%). From 2006 to 2016, diagnostic rates decreased for reflux and increased for GORD. Prescribing of acid suppressants occurred in 43.6% visits for reflux and 48.5% visits for GORD, similar to rates of counselling, advice or education (reflux: 38.5%, GORD: 43.4% of visits). Prescribing of PPIs increased (statistically significant only for visits for reflux), while prescribing of H2RAs decreased. Conclusions: Overprescribing of acid suppressants to infants may be occurring. In infants, acid-suppressant medicines are no better than placebo and may have significant negative side effects; however, guidelines are inconsistent. Clear, concise and consistent guidance is needed. GPs and parents need to understand what is normal and limitations of medical therapy. We need a greater understanding of the influences on GP prescribing practices, of parents' knowledge and attitudes and of the pressures on parents of infants with these conditions.